(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background:- The word “hernia” derived from Latin term meaning “a rupture”[1]. A hernia is defined as an area of weakness or complete disruption of fibromuscular tissue of body wall can pass through or herniate through defect[1]. In all ventral abdominal hernias, Inguinal hernia is the most common. Inguinal hernia repair is common in surgical practice. In past, the repair was pure open tissue repair which was changed to open prosthetic mesh repair. Laparoscopic groin hernia repair was first performed by Ger in 1979[1]. The laparoscopic approach to hernia repair has since evolved into common and effective procedure. Methods:- The presented study is a prospective, open labelled, randomized, comparative study during a period from May-2017 to March-2019. After taking written consent from the patients were randomly allocated to two groups. Group A, Open hernioplasty were operated with open tension free Lichtenstein’s hernioplasty. Group B, laparoscopic hernioplasty were operated with Transabdominal Preperitoneal(TAPP) repair. Those patients who fulfilled the inclusion criteria are included in study. The mode of presentation, surgical treatment and postoperative complications were all evaluated and compared. Results:- During the study there were no major life threatening complications were reported in either group. The postoperative pain and need of analgesics, presence of surgical site infections were more in Open hernioplasty group compared to laparoscopy group. The time taken for return to routine daily activities and work was earlier in patients treated with laparoscopy compared to open surgery and good cosmetic results. Conclusions:- Laparoscopic hernia repair has better, evolving & effective procedure in recent days compared to open hernia repair in terms of less postoperative complications, early recovery with good cosmetic results.